2006
DOI: 10.2174/138620706776055458
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretagogues

Abstract: Growth hormone secretagogues (GHSs) are synthetic molecules that stimulate and amplify pulsatile pituitary growth hormone release, via a separate pathway distinct from GH releasing hormone/somatostatin. The activity of GHSs is not fully specific for GH secretion; some GHSs also have slight releasing activity on other pituitary hormones and mediate GH independent biological activities. The first GHSs were discovered in 1977. Since then, an intensive research to synthesize a potent oral GHSs has been undertaken.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Most recently, shorter peptides derived from D -Arg 1 - D -Phe 5 - D -Trp 7,9 -Leu 11 -substance P were shown to display inverse agonist activity on GHS-R1a as well [131]. Finally, GHS-R1a antagonists are also available, such as D -Lys 3 -GHRP-6, L765-867 [6, 7, 120], isoxazole, diaminopyrimidine and triazole derivatives [132,133,134]. Antibodies and RNA-Spiegelmers have been also developed for the blockade of GHS-R1a activity [135, 136].…”
Section: Type 1a Ghs Receptormentioning
confidence: 99%
See 3 more Smart Citations
“…Most recently, shorter peptides derived from D -Arg 1 - D -Phe 5 - D -Trp 7,9 -Leu 11 -substance P were shown to display inverse agonist activity on GHS-R1a as well [131]. Finally, GHS-R1a antagonists are also available, such as D -Lys 3 -GHRP-6, L765-867 [6, 7, 120], isoxazole, diaminopyrimidine and triazole derivatives [132,133,134]. Antibodies and RNA-Spiegelmers have been also developed for the blockade of GHS-R1a activity [135, 136].…”
Section: Type 1a Ghs Receptormentioning
confidence: 99%
“…Accordingly, it was hypothesized that the GH-releasing effect of the D -Trp 2 GHRP reflected the activity of an unknown endogenous factor or hypophysiotropic hormone distinct from growth hormone-releasing hormone (GHRH). The ability of the hexapeptide GHRP-6 to synergize with GHRH with remarkable potency in men [3], prompted the development of other GHRP-6 analogs (GHRP-1, GHRP-2 and hexarelin) with high potency [4,5,6] and some orally active peptido-mimetic GH secretagogues (GHS) such as the spiroperidine derivative MK-0677 [7,8,9,10,11,12]. Particularly remarkable is the broad range of chemistries of the GHS developed in the last few years by several pharmaceutical groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1976, it was revealed that modified opioid peptides had low GH secretory activity [2]. Since then, many efforts have been made to develop and improve potential applications of these GH secretagogues (GHSs) [37]. GHSs act on the pituitary and hypothalamus to release GH, not through the growth hormone releasing hormone receptor (GHRHR) but through an orphan receptor, the GHSR [8].…”
Section: Introductionmentioning
confidence: 99%